Manajemen Isu Penggelapan Uang Nasabah Bank Maybank Indonesia Dalam Memperbaiki Citra Perusahaan - Refanda Daffa Falika; Reza Septiansa Saputra; Rissa Aurelia Restiani; Tria Patrianti (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research examines a case of embezzlement of funds that occurred at PT Bank Maybank Indonesia 3 years ago which was experienced by an E-Sport Athlete and his mother. Bank Maybank Indonesia is a private bank With this case, the quality of banking has decreased and is considered inadequate by the public, especially customers. Therefore, issue management is needed regarding cases of embezzlement of funds which result in a bad company image. Apart from that, the aim of this research was to find out how to improve the company's image after the Maybank Indonesia embezzlement case. The research method used is a normative research method by examining data such as books, journals, articles and other data sources related to laws and regulations. Data collection is based on independent observation and independent literature.